Molecular and cellular analysis of immunity in the phytoplasma vector Euscelidius variegatus: exploiting immunity to improve biological control strategies - R Tedeschi (Invertebrate Survival Journal, 2017)
Insects depend on innate immunity only to defend themselves against pathogens and to regulate interactions with many other microorganisms, such as different kinds of symbionts. Recently, it has been suggested that immunocytes could play a role in the vectorial capacity of insects leading to an increased interest towards primary immunocyte cultures. We analysed at molecular and cellular level the immune response of the leafhopper Euscelidius variegatus with the aim to provide an in vitro model for studying the insect-microbe interactions. We in vitro cultured and kept alive for more than 3 months E. variegatus immunocytes that showed a mitotic capacity as well as adhesion and phagocytic activities. In situ hybridization revealed that the defensin gene is actively transcribed in cultured immunocytes, while cecropins were not recorded in this species. These promising results obtained with E. variegaus, a leafhopper frequently used as a laboratory experimental model of insect vector of phytoplasmas, will help in developing in vitro tools for the study of the interactions between these pathogens and their vectors. Key Words: innate immunity; circulating immunocytes; defensin, insect vectors; leafhopper